1994
DOI: 10.1016/1010-7940(94)90084-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrity and viability of homograft valves

Abstract: Since it has been suggested that the leaflet tissue viability influences durability after homologous valve replacement, we compared different harvest and preservation techniques in order to examine the quality and smoothness of homograft conservation. We analyzed human aortic and pulmonary valve leaflets obtained from 'heart-beating donors' (HBD) during heart transplantation and from 'non-heart-beating donors' (NHBD) during coroner's autopsies. Valves were either cryopreserved in liquid nitrogen or stored at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…One pathologist examined all specimens and described the endothelial integrity according to the score system proposed by Fischlein et al [6] using the following criteria: (1) completely confluent endothelium; (2) partially confluent endothelium; (3) loosely netted endothelium; (4) islands of endothelium; and (5) no endothelium. .…”
Section: Preparation For Scanning Electron Microscopymentioning
confidence: 99%
“…One pathologist examined all specimens and described the endothelial integrity according to the score system proposed by Fischlein et al [6] using the following criteria: (1) completely confluent endothelium; (2) partially confluent endothelium; (3) loosely netted endothelium; (4) islands of endothelium; and (5) no endothelium. .…”
Section: Preparation For Scanning Electron Microscopymentioning
confidence: 99%
“…[13] The use of biological materials for patients with aortic PVE is recommended due to the low reinfection rates caused by the increased penetration of antibiotics in these tissues and the presence of viable cells. [14] Hagl et al [15] reported their experience regarding the use of a mechanical prosthesis in patients with PVE of the aortic valve and identified a mortality rate of 11% in 28 patients. They only had one recurrent case (4%) that died during the reoperation, and this happened at the postoperative third month.…”
Section: Discussionmentioning
confidence: 99%
“…artery has a long-lasting impact on survival after CABG [3][4][5]. Thrombosis and/or vasospasm of the ITA in the postoperative period [6,7] and the development of intimal proliferation and atherosclerosis years after coronary artery bypass surgery have previously been reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrathin sections were collected on copper grids, stained with uranyl acetate and lead citrate and examined with a Jeol JEM 1200EX (Japan) transmission electron microscope and finally were observed. One blinded anatomopatholog examined all specimens and described the endothelial integrity according to the score system proposed by Fischlein et al [3] using the following criteria: 1) completely confluent endothelium; 2) partially confluent endothelium; 3) loosely netted endothelium; 4) islands of endothelium; and 5) no endothelium.…”
Section: Preparation For Tranmission Electron Microscopymentioning
confidence: 99%